Analisis Implementasi Pendidikan Inklusif di Provinsi Aceh: Budaya, Kebijakan, dan Pelaksanaan - Muhammad Haekal (STAI Terpadu Yogyakarta, 2021)
This study analyzed the implementation of inclusive policies in Aceh Province starting from 2012 to 2020. The analysis was based on three aspects: culture, policy, and implementation. This study used a qualitative approach, in which the document analysis was applied as the primary method in this research. The document used was the Aceh Governor Regulation No. 92 of 2012 on the Implementation of Inclusive Education. The study results stated that the Aceh Government had not appropriately implemented the three elements of inclusive education in Aceh. The Aceh government had to strive to develop the foundation of inclusive education. This study suggests that the local government of Aceh should implement inclusive education using the Index for Inclusion and start by strengthening an inclusive culture before moving on to policy and implementation.